MODEL AUTOKATALISIS PERUBAHAN WARNA TOMAT SELAMA PENYIMPANAN DENGAN PENAMBAHAN KMnO4 DAN ARANG AKTIF BAMBU SEBAGAI ETHYLENE SCAVENGER - Ediati, Rifah; Siswantoro, Siswantoro; Al Hamid, , Nur Nadiyatul Fitriyah (Journal of Agricultural and Biosystem Engineering Research, 2023)
The color of fresh tomatoes is a key factor influencing consumer acceptance. Many postharvest techniques were aimed at preserving the orange to pink color range. Despite this, the prediction model for tomato color changes during storage has received little attention. Such a model would be invaluable in assessing natural color changes, as well as the impact of post-harvest treatments. To address this gap, we conducted a study involving the storage of untreated tomatoes and those treated with ethylene scavenger (ES). ES was made from a mixture of active bamboo charcoal and KMnO4. The tomatoes were packaged in cardboard containing 2 grams, 4 grams, or 6 grams of ES and then stored at room temperature for 10 days. We analyzed changes in tomato color daily during this period. Our results indicate that changes in brightness and yellow color followed a first-order autocatalysis kinetic model, while changes in red color followed a logistic model. The most effective treatment involved 2 grams of ethylene scavenger, as indicated by the smallest k value for changes in brightness, yellow color, and red color. The addition of ethylene scavenger effectively inhibited the decrease in tomato brightness and yellow color, while increasing red color. Overall, our findings suggest that ethylene scavenger treatment can effectively preserve tomato color during storage. Keywords: tomato, bamboo activated charcoal, KMnO4, ethylene scavenger.